Critical Examination of Halal Industry Policy In Indonesian - Moh Zaenal Muttaqin; Nurodin, Nurodin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The halal industry is a derivative of the sharia economic concept that has grown in Indonesia since the 1990s. Sharia economics is a value extracted from primary sources (the Koran and hadith) in Islam, and